The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1109/tec.2018.2831692
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Voltage Regulation of Multiinfeed VSC-HVDC on Power System Stability

Abstract: Due to the anticipated proliferation of HVDC links up to and beyond 2020 into transmission systems, it is expected that in some locations, two or more HVDC links will be installed with a short electrical distance between them and will form a multiinfeed (MI)-HVDC scenario for the system. The control and operation of MI-HVDC systems are of particular concern for weak grids such as that likely to be found in the North of Scotland network. It is shown that the ac voltage regulation in the VSC-HVDC link may advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…However, the study of [8][9][10] implies that the AC voltage regulation in the VSC-HVDC link may adversely affect the dynamic performance of the AC system. The reported case studies in [8] indicate that the embedded VSC-HVDC grid can aggravate interarea oscillations of the host AC system without supplementary control and based on the conventional dq-frame control structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the study of [8][9][10] implies that the AC voltage regulation in the VSC-HVDC link may adversely affect the dynamic performance of the AC system. The reported case studies in [8] indicate that the embedded VSC-HVDC grid can aggravate interarea oscillations of the host AC system without supplementary control and based on the conventional dq-frame control structure.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it is found that AC voltage control affects the damping of power system oscillations little. The work in [10] shows that the AC voltage regulation in the VSC-HVDC link may adversely affect the dynamic performance of the host weak AC system under the multi-infeed VSC-HVDC scenario.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it will allow to for example automatically identify the over/under and loading elements in the power grid, also it can help to identifies exactly the suitable bus that can carry the new load. [27][28][29][30][31][32][33][34][35][36][37][38]. Moreover, DIgSILENT PowerFactory offers a range of load flow calculation methods, including a full AC Newton-Raphson technique (balanced and unbalanced) and a linear DC method.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors use the DIgSILENT as a benchmark to simulate and to analyze the power system load flow problem [27][28][29][30][31], Newton-Raphson Load flow method modeling by using DIgSILENT is explained in [27,28]. For load flow study and grid simulation, the DIgSILENT is preferred and is recommended in a comparison between many software packages that is because it behaved as it is expected [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%